Isolation, Identification and the Abilities of Fungi Associated with Agarwood from Bangka Belitung Island to Induce Agarwood Compounds - Hartono Hartono; Arif Wibowo; Achmadi Priyatmojo (Jurnal Perlindungan Tanaman Indonesia, 2019)
Agarwood is one of the non-timber forest products that have high economic value. Agarwood is widely used to make incense, perfume and other products. Sapwood on agarwood is a group of secondary metabolites of agarwood plants that form a lump and have a certain color and aroma. The fragrant aroma of sapwood on agarwood is formed due to pathogenic infection of the agarwood tree. Until now, most studies of fungi forming sapwood are only oriented to virulent pathogenic fungi in nature and have never been reported to form hypovirulent agarwood. This study aimed to evaluate the potential of fungi originating from sapwood on agarwood especially those that are hypovirulent in inducing sesquiterpene compounds. This study included exploration, isolation, identification, and induction of fungi associated with sapwood on agarwood from four districts in the Bangka Belitung Islands Province. Hypovirulence test in cucumber sprouts and sesquiterpene induction test on agarwood plantlets was conducted in the laboratory. Based on the isolation results, 48 fungal isolates associated with sapwood on agarwood were found: fungi of genus Fusarium, Trichoderma, Aspergillus, Penicillium, Curvularia, Peniophora, and six isolates were unidentified. Based on the hypovirulence test on cucumber sprouts, 46 isolates of the fungus 46 isolates were virulent and 2 isolates were hypovirulent (isolates 4A and 17A). The induction of sesquiterpene compounds on the agarwood plant was employed using 5 sample isolates consisting of 4 virulent isolates (2A, 7A, 18A, and 25A) and 1 hypovirulent isolate (Isolate 4A). The results showed that hypovirulent isolates were able to produce sesquiterpenes even in small amounts compared with virulent isolates. Isolates produced many sesquiterpene compounds were isolates 18A (Fusarium sp.). Sesquiterpene compounds formed were pinene, terpineol, patchouli alcohol, trimethyl-naphthalene, beta-caryophyllene, camphor, eugenol, trimethyl- benzene, phenanthrene, citronella, eucalyptol, 4-hydroxy-4-methyl-2-pentanone. In this study also found fungi associated with sapwood on agarwood which had never been reported by previous researchers, Peniophora sp. (isolate 25A).